Sleep Problems Are Related to a Worse Quality of Life and a Greater Non-Motor Symptoms Burden in Parkinson's Disease. (November 2021) - Santos-García, Diego; Castro, E. Suárez; de Deus Fonticoba, T.; Panceiras, M. J. Feal; Enriquez, J. G. Muñoz; González, J. M. Paz; Bartolomé, C. Cores; Planellas, L. L.; Caldentey, J. García; Caballol, N.; Legarda, I.; López, I. Cabo; et al.
Introduction: The aim of the present study was to examine the frequency of self-reported sleep problems and their associated factors in a large cohort of PD patients. Methods: PD patients and controls, recruited from 35 centers of Spain from the COPPADIS cohort were included in this cross-sectional study. Sleep problems were assessed by the Spanish version of the Parkinson's disease Sleep Scale version 1 (PDSS-1). An overall score below 82 or a score below 5 on at least 1 item was defined as sleep problems. Results: The frequency of sleep problems was nearly double in PD patients compared to controls: 65.8% (448/681) vs 33.5% (65/206) (p < 0.0001). Mean total PDSS score was lower in PD patients than controls: 114.9 ± 28.8 vs 132.8 ± 16.3 (p < 0.0001). Quality of life (QoL) was worse in PD patients with sleep problems compared to those without: PDQ-39SI, 19.3 ± 14 vs 13 ± 11.6 (p < 0.0001); EUROHIS-QoL8, 3.7 ± 0.5 vs 3.9 ± 0.5 (p < 0.0001). Non-motor symptoms burden (NMSS; OR = 1.029; 95%CI 1.015–1.043; p < 0.0001) and impulse control behaviors (QUIP-RS; OR = 1.054; 95%CI 1.009–1.101; p = 0.018) were associated with sleep problems after adjustment for age, gender, disease duration, daily equivalent levodopa dose, H&Y, UPDRS-III, UPDRS-IV, PD-CRS, BDI-II, NPI, VAS-Pain, VAFS, FOGQ, and total number of non-antiparkinsonian treatments. Conclusion: Sleep problems were frequent in PD patients and were related to both a worse QoL and a greater non-motor symptoms burden in PD. These findings call for increased awareness of sleep problems in PD patients.